On the History of Words Meaning “a Horse” in the Russian and Byelorussian Languages - Аронайте, Л. (Kalbotyra, 1973)
The following article deals with the investigations of lexico-semantic group of words meaning “a horse” in the Russian and Byelorussian languages. On the basis of the Moscowtranslated edition of the Lithuanian Statute, the Lithuanian Statute and Russian, Byelorussian and Polish dictionaries the terminological process of the two closely related languages is being investigated.In the early 17th century the Russian and Byelorussian languages possessed specific systems of means to express the concept of “a horse”. The majority of words, slavonic by origin, is the property both of the Russian and Byelorussian languages. Nevertheless, one can notice differences in quality and quantity. The differences in quantity are noticed in non-coincidence of the volume of the meanings (the Byelorussian “конь” has a wider meaning than the Russian “конь”, the Byelorussian “кабыла” has a narrower meaning than the Russian “кабыла”). The semantic links of these lexemes in both languages differ as well.The terminilogical specifies are expressed in different distribution of the analysed lexics on the level of the terminologic and nonterminologic speech.In the process of the historical development of the words meaning “a horse” certain semantic glides took place inside the analysed lexico-semantic group, they were caused by the appearance or disappearance of a separate word or its meaning. Such lexico-semantic changes in each concrete language are directed towards the forming of national terminology.